Locus of Control Among Arab and Jewish Israeli Parolees - Peled-Laskov, Ronit (International journal of offender therapy and comparative criminology, 2025)
This research examines how participation in the Israeli Prisoner Rehabilitation Authority supervised therapy program for paroled prisoners can reinforce Jewish and Arab prisoners’ locus of control given their cultural diversity. Research participants included 108 paroled prisoners who had taken part in the program during 2019 to 2020. The program appears to have made a positive contribution to participants’ locus of control, particularly among Jewish parolees. For Arab parolees, the program’s strongest contribution was alleviating their apprehensions about returning to prison. Possible Theoretical explanations are offered for this finding, by referring to the concept of “culture-sensitive care” and the potential contribution of a change in perspective regarding the process of ending delinquency.